A profile in FIRE: resolving the radial distributions of satellite galaxies in the Local Group with simulations. Issue 1 (31st October 2019) - Samuel, Jenna; Wetzel, Andrew; Tollerud, Erik; Garrison-Kimmel, Shea; Loebman, Sarah; El-Badry, Kareem; Hopkins, Philip F; Boylan-Kolchin, Michael; Faucher-Giguère, Claude-André; Bullock, James S; Benincasa, Samantha; Bailin, Jeremy
ABSTRACT: While many tensions between Local Group (LG) satellite galaxies and Λ cold dark matter cosmology have been alleviated through recent cosmological simulations, the spatial distribution of satellites remains an important test of physical models and physical versus numerical disruption in simulations. Using the FIRE-2 cosmological zoom-in baryonic simulations, we examine the radial distributions of satellites with M_*10^5 M⊙ around eight isolated Milky Way (MW) mass host galaxies and four hosts in LG-like pairs. We demonstrate that these simulations resolve the survival and physical destruction of satellites with M_*10^5 M⊙ . The simulations broadly agree with LG observations, spanning the radial profiles around the MW and M31. This agreement does not depend strongly on satellite mass, even at distances ≲100 kpc. Host-to-host variation dominates the scatter in satellite counts within 300 kpc of the hosts, while time variation dominates scatter within 50 kpc. More massive host galaxies within our sample have fewer satellites at small distances, likely because of enhanced tidal destruction of satellites via the baryonic discs of host galaxies. Furthermore, we quantify and provide fits to the tidal depletion of subhaloes in baryonic relative to dark matter-only simulations as a function of distance. Our simulated profiles imply observational incompleteness in the LG even at M_*10^5 M⊙ : we predict 2–10 such satellites to be discovered around the MW and possibly 6–9 around M31. To provide cosmological context, we compare our results with the radial profiles of satellites around MW analogues in the SAGA survey, finding that our simulations are broadly consistent with most SAGA systems.